(untitled) (Economic studies journal, 2019)
This study dealt with the subject of the training system adopted by the oil companies and its impact on the development and improvement of human skills (Al Waha Oil Company), and then addressing an important aspect which is not limited to the managers in the organization, but extends to all administrative levels in the organizational hierarchy of the organization, Specialized in the development of competencies, abilities and skills for all working individuals and the effectiveness of performance for their current jobs, preparation and rehabilitation to ensure the performance of their responsibilities in the face required to achieve high degrees of quality of performance. This study attempt to identify the impact of training in development skills and abilities of all employees at different levels of management in the organization, and the possibility of determining the types of training programs they need, which have a positive impact for all employees of the organization. The researcher used the questionnaire form as a tool for collecting data. The study concluded with a number of results that there is a positive relationship between training and the development and refinement of human competencies it found that (47.5%) of changes in the level of performance of workers caused by training.